Spirituality and Mental Health: A Review of Religion and Philosophy - Susi Puspita Sari; Fadhli Syam; Afriwes Afriwes; Ridwan Ridwan (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
The relationship between spirituality and mental health is a vital interdisciplinary field that bridges medicine, psychology, theology, and philosophy. This field explores how beliefs, values, practices, and transcendent experiences influence psychological well-being to complement a holistic approach to mental health that meets human needs. This study aims to develop and conduct a preliminary validity test of a brief Spiritual Assessment module for integration into psychological and psychiatric nursing practice in Indonesia. The module is designed to explore patients’ beliefs, practices, and spiritual communities, and to identify the role of spirituality as a source of strength or conflict. The study employed a structured and systematic literature review (SLR) to identify, evaluate, and synthesize relevant empirical evidence, yielding comprehensive and objective conclusions based on critical review to provide a strong, transparent, replicable, and subjectively unbiased theoretical foundation. First, empirical evidence establishes a significant positive correlation between spiritual engagement and reduced depression, anxiety, and stress as valid protective factors. Second, psychological mechanisms identify spirituality as a meaning-making system that fosters resilience, hope, and gratitude, and enhances self-agency through self-awareness and self-efficacy. Third, clinical applications emphasize the integration of spirituality into psychotherapy and biological psychiatry to improve adherence and coping. Fourth, a comprehensive review affirms the transformative nature of spirituality in fostering sustainable well-being beyond pharmacological interventions. This study concludes that there is strong empirical evidence demonstrating a positive correlation between spirituality and better mental health. These positive effects are mediated by specific psychological mechanisms such as meaning-making and increased resilience. The integration of spirituality into clinical practice is essential for effective holistic care. Spirituality plays a sustained, transformative role in supporting overall mental health through a holistic approach